2005
DOI: 10.1177/1087054705279305
|View full text |Cite
|
Sign up to set email alerts
|

Development of a School-Based Treatment Program for Middle School Youth With ADHD

Abstract: The authors conduct an evaluation of a middle school-based treatment program for youth with ADHD during early stages of treatment development. The studies focus on interpreting outcome trends in preliminary data and identifying assessment issues that will be important to consider when conducting a clinical trial. Parent reports indicate that the majority of students benefit from improvements in academic, social, and overall functioning. Although teachers report beneficial effects for the majority of the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 19 publications
6
83
1
4
Order By: Relevance
“…It is interesting that the endorsement of a performance-avoidance orientation was unique to students with ADHD and that the orientation declined over the course of the year. This decline corresponds with the typical pattern of declining grades that occur for students with ADHD over the course of the academic year (Evans, Langberg, Raggi, Allen, & Buvinger, 2005). Although these findings are not conclusive, they suggest that a performance-avoidance orientation may play a unique role with these students and potentially facilitate classroom achievement.…”
Section: Research Questionmentioning
confidence: 67%
“…It is interesting that the endorsement of a performance-avoidance orientation was unique to students with ADHD and that the orientation declined over the course of the year. This decline corresponds with the typical pattern of declining grades that occur for students with ADHD over the course of the academic year (Evans, Langberg, Raggi, Allen, & Buvinger, 2005). Although these findings are not conclusive, they suggest that a performance-avoidance orientation may play a unique role with these students and potentially facilitate classroom achievement.…”
Section: Research Questionmentioning
confidence: 67%
“…t statistic). For three studies that reported proportions rather than continuous data, [141][142][143] the log-odds ratio was converted into a SMD [for formula see URL: www.campbellcollaboration.org/ artman2/uploads/1/2_D_Wilson__Calculating_ES.pdf (accessed 16 December 2014)]. 144 For one study reporting change scores, the SMD was estimated by dividing the difference between the gain scores in each trial arm by the pooled SD while taking account of the pre-post correlations within each arm.…”
Section: Statistical Informationmentioning
confidence: 99%
“…144 For seven studies where the relevant empirical data were not reported or available from the study authors, only narrative synthesis was conducted. 141,162,180,186,191,192,198 All data were extracted by MR and checked by DM with all disagreements resolved successfully through discussion.…”
Section: Statistical Informationmentioning
confidence: 99%
See 2 more Smart Citations